Quantifying the impact of nuisance flooding on urban coastal communities under present and future climatic conditions: Norfolk, Virginia as a case study - Jiwoo Jeong; Sergio A. Barbosa; Jonathan L. Goodall (Journal of Hydrology: Regional Studies)
Study region: Norfolk, Virginia, United States Study focus: Nuisance flooding, characterized by frequent but minor floods, has been on the rise and the trend is expected to continue due to climate change. Utilizing a two-dimensional surface flow / one-dimensional pipe hydrodynamic model, this study presents a methodology for simulating flooding from low return period tidal and rainfall events to quantify the impact of nuisance flooding on urban coastal communities under present and future climatic conditions. Applying the methodology, the results show the impact of nuisance flooding from tidal alone and compound (i.e., rainfall and tide) events. New hydrologic insights for the region: Using 2020 as a base year, the model suggests tidal nuisance flooding (TNF) impacts approximately 4 % (1.87 km2) of the study area. With a projected 1-meter sea-level rise by 2100, the TNF extent is projected to increase to approximately 12 % (5.85 km2) — more than tripling the 2020 TNF extent. For the 2020 base year, when rainfall and high tide occur simultaneously, compound nuisance flooding (CNF) leads to 11 % (5.15 km2) of the study area being inundated. By 2100, the projected inundated area by CNF is estimated to be 20 % (9.41 km2). Overall, sea level rise drives the expansion of TNF along riverbanks and adjacent areas, while submerging many urban drainage system outlets. This prevents efficient rainfall drainage, which causes CNF on inland low-lying areas.